(untitled) (Bangladesh Journal of Medical Microbiology, 2023)
Background: Knowledge from pre-primary school about the prevention of dental caries is better before the disease process has starte. Objective: The purpose of this study was to observe the knowledge of oral health maintenance among the children of 6 to 9 years old such as regular tooth brushing, uses of oral hygiene aids and dental attendance to maintain their good oral health for a life time. Methodology: This cross-sectional study conducted in Dhaka Dental College and Hospital, Bangladesh study was carried out from October 2019 to September 2020. A total of 175 participants children aged 6-9 years attending at the OPD with dental Caries in Dhaka Dental College Hospital were the study population. The study population were Included Children aged 6 to 9 years in Dhaka dental college and hospital who were available and wished to participate. The questionnaire was used in this study pre-tested before the data collection, data was collected using semi-structured questionnaire by face-to-face interview. Results: A total of 175 participants children aged 6 to 9 years attending at the OPD with dental Caries in Dhaka Dental College Hospital were the study population. The knowledge according to the correct method of tooth brushing to keep healthy teeth which were significant with their age and education. The study revealed the knowledge according to the correct method of tooth brushing to keep healthy teeth which were not significant among both gender (P=0.000038) and level of education (P=0.00001). The knowledge according to cleaning teeth and mouth after each meal to keep healthy teeth which were significant only with their age (P=0.00027) and same as knowledge according the to relation of food or drinks with healthy teeth which were significant with their age(P=0 .00729) and education significant level (P=0.001185), the knowledge according to poor oral health causes of dental problem which were significant with their education level (P=0.002524) and knowledge to the necessity of dental check-up at least once in year which were significant with their age(P=0.04237) and education level (P=0.002524). Conclusion: In conclusion, it is found that a significant association between the education level and age of children have good knowledge of oral health hygiene to prevent dental caries among the young children who are more prone to develop the diseases. Bangladesh Journal of Medical Microbiology, January 2023;17 (1):15-20